Kualitas Jaringan dan Harga terhadap Minat Beli Kartu Telkomsel pada CV. Sinar Telekom Lahat - Hayani Hayani; Vemi Fytaloka (Journal of Management and Bussines (JOMB), 2024)
This study aims to investigate the effect of network quality and price partially and simultaneously on the purchase interest of Telkomsel cards at CV. Sinar Telekom Lahat. The data analysis method used is quantitative using multiple linear regression, where the model equation is Y = a + b1X1 + b2X2 + e. The results of the t-test analysis show that network quality (X1) has a significant effect on purchase interest (Y), while price (X2) does not have a significant effect on purchase interest (Y) of Telkomsel cards at CV. Sinar Telekom Lahat. Furthermore, the F test shows that simultaneously, network quality (X1) and price (X2) have a significant effect on purchase interest (Y). Conclusion, This study contributes to the understanding of the factors that influence consumer purchase interest in Telkomsel cards in a specific business environment. The implications of the results of this study can be used as a basis for a more effective marketing strategy to increase purchase interest in Telkomsel cards in the local market. Keywords: Price, Network Quality, Purchase Interest